Religion and politics in Europe, the Middle East and North Africa - Haynes, Jeffrey, 1953- (Routledge/ECPR studies in European political science, 2010)
In the early twenty-first century, it is now clear that religion is increasingly influential in the political realm in ways which call into question the principles and practices of secularism. The Iranian revolution of 1978-9 marked the decisive 'reappearance' of political religion in global politics, highlighting a major development which is the subject of this edited volume. Addressing a highly salient and timely topic, this book examines the consequences of political interactions involving the state and religious actors in Christian, Muslim and Judaist contexts. Building on.